Análisis de Riesgo Biomecánicos y de Alto Riesgo para los Trabajadores de la Empresa Construcol S.A.S (2022)
The objective of this research project was to carry out an analysis of biomechanical risk and highrisk work of the workers for the company Constructora de Obras civil Construcol SAS, with the purpose of elaborating recommendations that help in the promotion and prevention of the health of the workers. workers. This research is of a mixed type with a descriptive approach under the research line in integrated management systems, where the target population of the study was the workers who belong to the operating level of the company COSTRUCOL SA.S, which was taken as an analysis sample at the entire target population. The development of the research took place through the implementation of an interview in order to determine the level of impact of biomechanical risks and high-risk work where the intervention measures will be established from there an initial diagnosis will be generated indicating the Ergonometric flaws that existed in each job and that with this was intended to establish intervention measures that allow the company to define activities for the promotion and prevention of the health and well-being of its workers.